How aware are mothers about early childhood developmental milestones? A cross-sectional study at a maternity hospital in rural South India - Varghese, Suman Sarah; Merlyn Joseph,; Rachna Gohil,; Sanjana Thomas,; Sandra Mary Jose,; Presty Lukose,; Johnson, Avita Rose (Indian Journal of Child Health, 2020)
Background: Identification and intervention are pivotal in improving outcomes in cases of early childhood developmental delays (DDs). Mothers, as primary caregivers, are at a vantage point to recognize these delays early and seek prompt care. Objective: The objective of the study was to assess the awareness of early childhood developmental milestones (ECDMs) and identify factors that influence awareness among mothers of young children at a maternity hospital in rural South India. Materials and Methods: This was a cross-sectional study among mothers with a child under the age of 3 years, availing of health and immunization services at the rural hospital. The interview schedule included 4 items pertaining to risk factors associated with delayed milestones and 32 items regarding awareness of ECDM across four domains: Gross motor, fine motor, social, and language. Each correct answer was awarded 1 point. Results: Among 156 mothers, the mean ECDM awareness score was only 12.4 (±3.6), out of a maximum of 36. Awareness of some of the first milestones to be achieved in infancy was found to below. ECDM awareness score was significantly higher among mothers with higher levels of education (p=0.014) and among mothers who received health education on ECDM from community-level workers (p=0.038). Conclusion: Awareness among rural mothers regarding ECDM across all four developmental domains was found to be inadequate. Poor maternal awareness, of milestones that are the first to be achieved, is likely to result in delayed recognition and intervention for DD. Community-level workers must educate mothers regarding ECDM during immunization sessions and home visits, using the Mother and Child Protection Card as an educational tool.